2015
DOI: 10.1186/s13012-015-0303-4
|View full text |Cite
|
Sign up to set email alerts
|

Using a systematic review in clinical decision making: a pilot parallel, randomized controlled trial

Abstract: BackgroundEvidence suggests that systematic reviews are used infrequently by physicians in clinical decision-making. One proposed solution is to create filtered resources so that information is validated and refined in order to be read quickly. Two shortened systematic review formats were developed to enhance their use in clinical decision-making.MethodsTo prepare for a full-scale trial, we conducted a pilot study to test methods and procedures in order to refine the processes. A recruitment email was sent to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The next phases include completing a survey of perceptions of barriers and facilitators to use of systematic reviews by policy makers and health care managers in these provinces; integrating the survey and review results to develop a format for systematic reviews and test its usability using heuristic and individual usability testing; and conducting a randomised trial to assess a traditional systematic review format compared with the new format on the ability of health care managers and policy makers to understand the evidence in the review and apply it to a relevant health care decision-making scenario. We have done similar work to create a format for clinicians and found that it influences their ability to apply the evidence from a systematic review to a clinical scenario [ 20 , 60 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The next phases include completing a survey of perceptions of barriers and facilitators to use of systematic reviews by policy makers and health care managers in these provinces; integrating the survey and review results to develop a format for systematic reviews and test its usability using heuristic and individual usability testing; and conducting a randomised trial to assess a traditional systematic review format compared with the new format on the ability of health care managers and policy makers to understand the evidence in the review and apply it to a relevant health care decision-making scenario. We have done similar work to create a format for clinicians and found that it influences their ability to apply the evidence from a systematic review to a clinical scenario [ 20 , 60 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted that for future RCTs, recruitment may be more successful achieved from randomizing divisions versus individuals since the nature of policymaking is quite complex and often not completed at the individual level. Additionally, we identified other studies that were not focused on policymakers but rather, clinicians [34, 35] or the public [36]. These studies demonstrated that evidence summaries can improve understanding of research evidence within these populations; however, use of evidence in decision-making was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies are required to address barriers to research use, such as access, timeliness, user-friendliness and relevance of evidence [ 8 , 18 ], faced by decision-makers. In order to overcome such barriers, researchers have examined ways to effectively package the results from systematic reviews of intervention effectiveness to meet the needs of patients [ 19 21 ], healthcare professionals [ 22 24 ] and policy-makers [ 25 ]. For example, decision support aids and plain language summaries have been found to support the uptake of systematic review findings by patients and providers, respectively [ 21 ].…”
Section: Introductionmentioning
confidence: 99%